2015
DOI: 10.1002/chem.201502755
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium(I) Dimers Bearing Tripodal Diimine–Enolate Ligands: Proficient Reagents for the Controlled Reductive Activation of CO2 and SO2

Abstract: The first examples of magnesium(I) dimers bearing tripodal ligands, [(Mg{κ(3) -N,N',O-(ArNCMe)2 (OCCPh2 )CH})2 ] [Ar=2,6-iPr2 C6 H3 (Dip) 7, 2,6-Et2 C6 H3 (Dep) 8, or mesityl (Mes) 9] have been prepared by post-synthetic modification of the β-diketiminato ligands of previously reported magnesium(I) systems, using diphenylketene, OCCPh2 . In contrast, related reactions between β-diketiminato magnesium(I) dimers and the isoelectronic ketenimine, MesNCCPh2 , resulted in reductive insertion of the substrate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 36 publications
1
68
0
2
Order By: Relevance
“…In their recent investigation on the activation of CS 2 by [K(L)][(BDI Dipp,tBu )Ni(S)] (L = 18-C-6 or 2,2,2-cryptand), the Hayton group reported that following addition of a first CS 2 molecule to the nickel sulphide moiety, yielding trithiocarbonate, a further molecule of CS 2 is sequestered through C-C bond formation at the central methine carbon of the BDI ligand and yields an unexpected Ni derivative shown on Scheme 31. 138 Interestingly, the resulting tripodal monoanionic diamine-enolate skeleton has proven to be a good platform to support alkaline-earth and Ti chemistry. 77,137 In an analogous way, treatment of (BDI*)MgI (OEt 2 ) or (BDI*)Mg-Mg(BDI*) with diphenylketene yields the corresponding diamine-enolate cycloaddition products (Scheme 31).…”
Section: Metal-ligand Cross Addition Of Unsaturated Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…In their recent investigation on the activation of CS 2 by [K(L)][(BDI Dipp,tBu )Ni(S)] (L = 18-C-6 or 2,2,2-cryptand), the Hayton group reported that following addition of a first CS 2 molecule to the nickel sulphide moiety, yielding trithiocarbonate, a further molecule of CS 2 is sequestered through C-C bond formation at the central methine carbon of the BDI ligand and yields an unexpected Ni derivative shown on Scheme 31. 138 Interestingly, the resulting tripodal monoanionic diamine-enolate skeleton has proven to be a good platform to support alkaline-earth and Ti chemistry. 77,137 In an analogous way, treatment of (BDI*)MgI (OEt 2 ) or (BDI*)Mg-Mg(BDI*) with diphenylketene yields the corresponding diamine-enolate cycloaddition products (Scheme 31).…”
Section: Metal-ligand Cross Addition Of Unsaturated Substratesmentioning
confidence: 99%
“…136 Metal-ligand cooperative activation of ketene OvCvCPh 2 by the four-coordinate Ti(IV) imide (BDI*)Ti(NDipp)(OTf ) affords the tripodal diamine-enolate complex represented on Scheme 31. 77,137,138 The reactivity of (BDI*)Mg-Mg(BDI*) with OvCvCPh 2 is unique since other heteroallenes such as CO 2 , NCO and azides preferentially insert into the Mg-Mg bond. 138 Interestingly, the resulting tripodal monoanionic diamine-enolate skeleton has proven to be a good platform to support alkaline-earth and Ti chemistry.…”
Section: Metal-ligand Cross Addition Of Unsaturated Substratesmentioning
confidence: 99%
“…in 1 and 2. [3][4][5][6][7] In addition to these, a remarkable mixed valence More than being just chemical curiosities, dimeric magnesium(I) complexes, especially those incorporating β-diketiminate ligands, have been widely applied as soluble, selective and safe reducing agents in a diverse range of inorganic and organic synthetic transformations. [3] The growing popularity of these reagents lies with the fact that their use can lead to synthetic outcomes that are not achievable with traditional reducing agents, such as alkali metals, KC 8 and sodium naphthalide.…”
Section: L(thf)mg-mg(thf)l (R = Me; R' = Pr I ) and Lmg-mg(thf)l (R =mentioning
confidence: 99%
“…Alkali-und Erdalkalimetalle S Das ionische Supramolekül Li + @C 60 ⊂[10]CCP bildet sich bei der Reaktion von Li + @C 60 mit dem Cycloparaphenylen [10]CCP. Die Kristallstrukturanalyse bestätigt die vermutete 1:1-Komplexierung, wobei zwei kristallographisch unabhängige Li + @C 60 ⊂[10]CCP-Strukturen existieren.…”
Section: Anorganische Molekülchemieunclassified
“…In der Natriumverbindung (2) umgeben jeweils drei Chelatliganden die Ionen verzerrt oktaedrisch, die langen Na-P-Abstände (2,95 -3,03 Å) weisen (11). 10) Über Berylliumverbindungen ist im Vergleich zu den schweren Homologen relativ wenig bekannt. Jetzt gelang es, die beiden Berylliumcarbonate OCBeCO 3 und COBeCO 3 in einer Neonmatrix zu isolieren und zu untersuchen.…”
Section: Anorganische Chemie 2015unclassified